Importancia de un buen plan de gestión contable en una empresa. - Olivero Espinosa, Carlos Alexander (My University, 2022)
The accounting study is an essential element for a company, since the origin of time, accounting has become a fundamental element for the business future, the proper management of a good accounting plan, allows companies to take a good approach to decision-making and thus allow it to emerge in the long term. The conceptual method is based on Qualitative facts, since we rely on incurring in the situations of descriptive and narrative data collection, and the experiences obtained from other scientific articles. The main purpose of this project is to collect the necessary information, with the purpose of evaluating the future that will present us with a good systematic accounting management plan in a company and its development in business development, where we will focus on a representation of the balance sheet , since this financial statement is of the utmost importance, because it focuses us on how the assets, liabilities, income, expenses and cash flows of the companies are found. and its strategic focus is reflected in the insecurities of investors. Accounting finally concluded that for a company to function properly and efficiently, it is essential to take care together with the dependents. Put to that, it is resolved that for a company, accounting is a very important and very essential tool for its business development, but today, many of the entrepreneurs do not know how to identify these advantages that this science entails, and they do not give it the respective importance that accounting implies, strategic accounting plan.
El estudio contable es un elemento esencial para una empresa, desde el origen del tiempo, la contabilidad se a convertido en un elemento primordial para el porvenir empresarial, el manejo adecuado de un buen plan contable, permite a que las empresas tomen un buen enfoque para la toma de decisiones y así permitir que surja a largo plazo. Él método conceptual está basado en hechos Cualitativos, ya que nos basamos en incurrir en las situaciones de recolecciones de datos descriptivos y narrativos, y las experiencias obtenidas de otros artículos científicos. El propósito principal de este proyecto, es recolectar la información necesaria, con el propósito de evaluar el futuro que nos presentará un buen plan sistemático de gestión contable en una empresa y su desenvolvimiento en el desarrollo empresarial, donde nos enfocaremos en una representación del balance general, ya que es de suma importancia este estado financiero, porque nos enfoca en como se encuentran los activos, pasivos, ingresos, gastos y flujos de efectivos de las empresas. y su enfoque estratégico se plasma en las inseguridades de los inversionistas. Se concluyó, que para que una empresa funcione adecuadamente y de manera eficiente es, imprescindible un esmero en conjunto con los dependientes. Puesto a eso, se resuelve que para una empresa, la contabilidad es una herramienta muy importante y muy indispensable para su desenvolvimiento empresarial, pero hoy en día, muchos de los empresarios no saben identificar estas ventajas que conlleva esta ciencia, y no le dan la respectiva importancia que implica la contabilidad.
Keywords: PLAN CONTABLE; CONTABILIDAD; BALANCE GENERAL; ELEMENTOS PATRIMONIALES